Survey on ureTEric draiNage post uncomplicaTed ureteroscopy (STENT). Issue 2 (8th October 2020) - Bhatt, Nikita R.; MacKenzie, Kenneth; Shah, Taimur T.; Gallagher, Kevin; Clement, Keiran; Cambridge, William A.; Kulkarni, Meghana; MacLennan, Graeme; Manecksha, Rustom P.; Wiseman, Oliver J.; Mcclinton, Samuel; Smith, Daron; et al.
Abstract: Objectives: To assess the feasibility of conducting a randomised controlled trial (RCT) to assess whether avoiding ureteric drainage is superior to performing ureteric drainage after Uncomplicated Ureteroscopy and/or Flexible Ureterorenoscopy (URS/FURS) treatment of a urinary tract stone in improving patient reported outcome measures (PROMs) and 30‐day unplanned readmission rates. A secondary objective was to understand current practice of urologists regarding ureteric drainage after uncomplicated URS/FURS (UU). Material and methods: We undertook an online survey of urologists, circulated amongst members of international urological societies and through social media platforms. Uncomplicated URS/FURS was defined as completion of URS/FURS treatment for a urinary tract stone, with the absence of: ureteral trauma, residual fragments requiring further lithotripsy procedures, significant bleeding, perforation, prior urinary tract infection or pregnancy. The ureteric drainage options considered included an indwelling stent, stent on a string or a ureteric catheter. The primary outcome was to determine the proportion of urologists willing to take part in a RCT, randomising patients after UU to a "no ureteric drainage" arm or ureteric drainage arm. Secondary outcomes included determining in their current practice, the proportion of clinicians performing routine ureteric drainage after UU, the reasons for performing ureteric drainage following UU and their preferred optimal duration for ureteric drainage if it is used. The study was reported according to the Checklist for Reporting Results of Internet E‐Surveys (CHERRIES). Results: Total of 468 respondents from 45 countries took part in the survey, of whom 303 completed the entire survey (65%). The majority agreed that they would be willing to randomise patients (244/303, 81%) in the proposed RCT. Perceived lack of equipoise to randomise was the most common reason for not being willing to participate (59/303, 19%). 92% (308/335) reported that they use ureteric drainage after UU. This was most often due to wanting to prevent possible complications from post‐operative ureteric oedema (77%) or to aid passage of small fragments (43%). Complexity of the case (i.e. impacted stone 90%) and length of the procedure (46%) were the most important intraoperative factors influencing the decision to use ureteric drainage post procedure. If required, the median stated ideal duration of ureteric drainage was 5 days (IQR: 3–7 days) after UU. If having UU personally, 30% would want no stent postoperatively and over half would prefer a stent on a string. Conclusion: We have highlighted wide variation in practice regarding ureteric drainage after UU. Our results support the feasibility of an RCT evaluating if no ureteric drainage is superior to ureteric drainage in improving PROMs and 30‐day unplanned readmission rates following UU.